Financial management practices and performance of smes in sri lanka evidence from jaffna district - Yogendrarajah, R.; Kengatharan, L.; Jeyan Suganya, D.F. (University of Jaffna, 2017)
Efficient financial management practices is essential for small and medium enterprises to reach growth stage of the firm as it has major effect on performance. The aim of this study is to find out the financial management practices among small and medium sized enterprises in Jaffna district and also examine the impact of financial management practices on performance of SMEs. Financial management practices have been measured by working capital management, investment appraisal, capital structure management, financial reporting and analysis and accounting information system. Performance has been measured by perceptions on performance of owner of SMEs. Stratified random sampling method was used to select the participants from registered SMEs in Jaffna district. Data was collected through the self administered questionnaire from 60 SMEs functioning in Jaffna district. Descriptive and inferential statistics were used to analyze the data using SPSS. Cronbach's Alpha was used to check the reliability of the data. Results of the study revealed that there is a significant difference in the application of financial management practices between small and medium enterprises. Financial management practices of working capital management, investment appraisal, capital structure management, financial reporting and analysis and accounting information system are highly applied by medium sized enterprises than small enterprises. Working capital management and capital structure management have significant impact on SMEs performance. Outcome of the study may be useful to the practitioners to focus the financial management practices in order to enhance their business performance.
Keywords: Financial management practices; Performance; SMEs